Study of Sustainability and Water Management Indicators in the Municipalities of Araraquara, Jaú and São Carlos - Protásio, Júlia Ramos; Ventura, Katia Sakihama (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Understanding and effectively managing the quantity and quality of water on a regional scale, especially in basin regions, is extremely important to ensure the resilience of a municipality in the face of climate change. In this context, the objective was to study sustainability and water management indicators in the municipalities of Araraquara, Jaú and São Carlos, located in the central region of São Paulo (SP). The method was based on the characterization of the study area through bibliographical research and documentary analysis of information and secondary data, of both qualitative and quantitative nature. Next, water availability (Falkenmark index), water security (Urban Water Security Index) and sustainable development (Sustainability and Cities Development Index) were analyzed. The results indicated that water availability in the basin presents some seasonal problems of water supply and quality, with adverse effects during severe droughts. Regarding water security, all municipalities had indexes classified as 'High'. The observed sustainability gave an overall “average” rating for the three municipalities studied. It was concluded that, through the analysis of the selected indicators regarding the effectiveness of their integrated application in water management in the municipalities of Araraquara, Jaú and São Carlos, this study provided a comprehensive understanding of each municipality. The individual analysis of the municipalities revealed distinct characteristics and opportunities for improvements in the water resources sector
Keywords: Water Resources; Sustainability Indicators; Climate Change